Evaluation of amoxicillin, metronidazole and gentamicin dosage regimens for use in antibiotic prophylaxis in colorectal surgery. (20th September 2021) - da Silva Neto, M J J; MacKay, G; Agaram, R; MacLeod, M; Watson, D G; Thomson, A H
Abstract: Objectives: To evaluate amoxicillin, metronidazole and gentamicin dosage regimens for antibiotic prophylaxis in colorectal surgery. Methods: The study was conducted in 20 patients undergoing colorectal surgery. Patients received one or two doses of amoxicillin 1000 mg, metronidazole 500 mg and gentamicin 3 mg/kg ideal body weight, banded by height. Antibiotic concentrations were measured up to 7 h post dose. Population pharmacokinetic (PopPK) analysis with NONMEM followed by Monte Carlo simulation of different dosage regimens was used to estimate the PTA for potential organisms associated with surgical site infections (SSIs). Results: A median of 5 (range 3–6) concentrations were available per patient. CL and V of all antibiotics were related to weight; gentamicin CL was also related to CLCR . The administered doses maintained the desired PTA up to 8 h for the Streptococcus anginosus group but not for enterococci, Bacteroides fragilis group, MSSA, and Escherichia coli . An additional 500 mg amoxicillin every 4 h was sufficient to achieve the PTA for most relevant organisms but 2 hourly dosing was required for patients at risk of infective endocarditis. A metronidazole dose of 1000 mg was required for patients >85 kg. In patients with CLCR >50 mL/min, 5 mg/kg gentamicin (with an additional 2.5 mg/kg in prolonged surgery at 6 h) maintained PTA targets for >10 h. Conclusions: PopPK analysis with Monte Carlo simulation identified prophylactic antibiotic regimens that would maintain the PTA for organisms associated with SSIs during short- and long-duration colorectal surgery.